2012
DOI: 10.1016/j.febslet.2012.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of an indole‐diterpene gene cluster for lolitrem B biosynthesis in the grass endosymbiont Epichloë festucae

Abstract: Epichloë festucae Fl1 in association with Lolium perenne synthesizes a diverse range of indole‐diterpene bioprotective metabolites, including lolitrem B, a potent tremorgen. The ltm genes responsible for the synthesis of these metabolites are organized in three clusters at a single sub‐telomeric locus in the genome of E. festucae. Here we resolve the genetic basis for the remarkable indole‐diterpene diversity observed in planta by analyzing products that accumulate in associations containing ltm deletion mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 28 publications
5
85
0
Order By: Relevance
“…They suggested that LtmE catalyzes the di-prenylation of the A-ring of terpendole I, a paxilline-related compound, at positions, 20 and 21. 40) In the present study, AmyD was found to catalyze regular di-prenylation at the same positions of paxilline (Fig. 5).…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…They suggested that LtmE catalyzes the di-prenylation of the A-ring of terpendole I, a paxilline-related compound, at positions, 20 and 21. 40) In the present study, AmyD was found to catalyze regular di-prenylation at the same positions of paxilline (Fig. 5).…”
Section: Discussionsupporting
confidence: 59%
“…The other one showed high similarity to LtmJ (64% identity), a cytochrome P450 monooxygenase, which has been reported to be responsible for lolitremanes formation. 40) In sum, it is suggested that the cluster identified in this study participates in the generation of a lolilline/ lolitrem type of compound. To confirm this, the same strategy used for functional analysis of the paxilline biosynthetic gene cluster, the introduction of the pax genes into A. oryzae and an analysis of the compound produced by the transformant, 23) might be also useful.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Moreover, the very low Km value for DMAPP reasonably supports the result that farnesyl diphosphate and GGDP were not accepted as substrates. On the other hand, the Km value for paxilline was calculated to be higher than for DMAPP, suggesting that paxilline-related compounds, such as paspaline, 13-desoxypaxilline, lolitrems (Saikia et al 2012), and terpendoles (Motoyama et al 2012), might be accepted by PaxD.…”
Section: Discussionmentioning
confidence: 99%
“…No structural or detailed mechanistic information is available for prenyl cyclases involved in the biosynthesis of indole diterpenoids [47,[54][55][56] and of some meroterpenoids [57][58][59].…”
Section: C40 -Phyotenementioning
confidence: 99%